Modulation of low-dose ozone and LPS exposed acute mouse lung inflammation by IF1 mediated ATP hydrolysis inhibitor, BTB06584 - Singh, Pahul; Aulakh, Gurpreet Kaur (Frontiers in Immunology, 2023)
Ozone and bacterial lipopolysaccharide (LPS) are common air pollutants that are related to high hospital admissions due to airway hyperreactivity and increased susceptibility to infections, especially in children, older population and individuals with underlying conditions. We modeled acute lung inflammation (ALI) by exposing 6-8 week old male mice to 0.005 ppm ozone for 2 h followed by 50 μg of intranasal LPS. We compared the immunomodulatory effects of single dose pre-treatment with CD61 blocking antibody (clone 2C9.G2), ATPase inhibitor BTB06584 against propranolol as the immune-stimulant and dexamethasone as the immune-suppressant in the ALI model. Ozone and LPS exposure induced lung neutrophil and eosinophil recruitment as measured by respective peroxidase (MPO and EPX) assays, systemic leukopenia, increased levels of lung vascular neutrophil regulatory chemokines such as CXCL5, SDF-1, CXCL13 and a decrease in immune-regulatory chemokines such as BAL IL-10 and CCL27. While CD61 blocking antibody and BTB06584 produced maximum increase in BAL leukocyte counts, protein content and BAL chemokines, these treatments induced moderate increase in lung MPO and EPX content. CD61 blocking antibody induced maximal BAL cell death, a markedly punctate distribution of NK1.1, CX3CR1, CD61. BTB06584 preserved BAL cell viability with cytosolic and membrane distribution of Gr1 and CX3CR1. Propranolol attenuated BAL protein, protected against BAL cell death, induced polarized distribution of NK1.1, CX3CR1 and CD61 but presented with high lung EPX. Dexamethasone induced sparse cell membrane distribution of CX3CR1 and CD61 on BAL cells and displayed very low lung MPO and EPX levels despite highest levels of BAL chemokines.